Studi Komparasi Perilaku Masyarakat dalam Upaya Pencegahan Demam Berdarah Dengue terhadap Keberadaan Nyamuk sebagai Vektor - Briliana Nur Rohima, Sutami Budi Fitriawan, Puti Neila Kharisma Abbas,; Kusuma Dewi, Hanif, Karttegayen,Nabilah, Rizka Aries Putranti,Laxmiprita Pusparani Rahardjo,; Ayu Wikan Sayekti Agung Prasetyo Wicaksono Wahyudi Istiono (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Background: Dengue Hemorrhagic Fever (DHF) is one of the main public health problems in Indonesia. It canaffect all age groups and may lead to death especially in children. The data shows that DHF cases in KecamatanMantrijeron between January-June 2010 have reached the highest number of cases in past seven years, about94 cases. Kecamatan Mantrijeron has an increasing trend of DHF which make it possible for the occurrence ofan outbreak of DHF when no preventions are done. RW 17 Kelurahan Suryodiningratan and RW 02 KelurahanGedongkiwo are areas with highest prevalence. There are 8 and 9 cases in each area respectively.Objective: To compare community behavior in preventing the existence of mosquitoes that is a DHF vector in theenvironment of Kelurahan Suryodiningratan and Gedongkiwo, Kecamatan Mantrijeron.Method: This research was a descriptive observational study, with cross-sectional retrospective study designin July-August 2010 in RW 17 Kelurahan Suryodiningratan and RW 02 Gedongkiwo, Kecamatan Mantrijeron,Kotamadya Yogyakarta. The research target population was 379 head of family (HF) from RW 17 KelurahanSuryodiningratan and 360 HF from RW 02 Kelurahan Gedongkiwo. Samples used was 60 HF from RW 17Kelurahan Suryodiningratan and 66 HF from RW 02 Kelurahan Gedongkiwo (minimal sampling with P=0.5 were58 HF for RW 17 and 57 HF for RW 02). Sampling was done by random sampling with milestone technique, thebehavior questionnaire, and observational checklist of mosquito existence as the instrument. Independentvariables were six behavioral criteria; dependent variable was the existence of mosquitoes. Data analysis wasdone with bivariate analysis using relative risk (RR) and odds-ratio (OR).Results: Analysis result of correlation between behavior to existence of mosquitoes in RW 17 with RR andOR>1 are: 1. Not routinely inspecting larvae in water reservoir (RR=1.38 and OR=1.89) and 2. Not cleaning thebathtub once a week (RR=1.32 and OR=1.74). Analysis result of correlation between behavior to existence ofmosquitoes in RW 02 with RR and OR>1 are: 1. Not getting rid of bottles and cans (RR=1.66 and OR=3.89); 2. Notclosing all water reservoir (RR=3.21 and OR=17.55); 3. Not routinely inspecting larvae in water reservoir(RR=2.36 and OR=-); 4. The behavior of not cleaning the bathtub once a week (RR=2.07 and OR=-); 5. Thebehavior of not draining-up the bath tub when cleaning (RR=2.03 and OR=-); 6. The behavior of not brushingwater reservoir when cleaning (RR=1.94 and OR=-). The difference between both districts is the characteristicof RW 17 Kelurahan Suryodingratan that is abundant in trees as the rest area for mosquitoes and the riverbanksof RW 02 Kelurahan Gedungkiwo are filled with household wastes.Conclusion: There are differences in behavior in preventing mosquito existence in both RW 17 KelurahanSuryodiningratan and RW 02 Kelurahan Gedongkiwo. The population of Kelurahan Gedongkiwo regularly disposesbottles and cans, drains the bath tub when cleaning, brushes water reservoir when cleaning, closes all waterreservoir, inspects larvae in water reservoir and cleans the bathtub once a week to prevent mosquitoes. Thepopulation of Kelurahan Suryodiningratan inspects larvae in water reservoir and cleans the bathtub once aweek to prevent mosquitoes.Keywords: Dengue Hemorrhagic Fever, behavior, RW 17 Kelurahan Suryodiningratan and RW 02 KelurahanGedongkiwo, Kecamatan Mantrijeron